Mengembangkan Kepribadian Empati Guru Pendidikan Agama Islam dalam Kurikulum K13 di SDN 06 LALAN - Olvy Mailandari; Sutipyo Ru’iya (STAI Terpadu Yogyakarta, 2022)
In education, professional educators are needed in their attitudes, one of which is the personality of the educator in being empathetic to their students. For this reason, this paper was made solely to teach students to be empathetic, especially in the teaching and learning process. An educator is required to have more knowledge. and good communication skills for that an educator must have a good empathetic attitude, educators are role models for their own educators The problem is that a student lacks interaction with his students so that communication is not good, this results in a gap in educator empathy in enforcing the rules towards students, so that educators are not able to understand what is experienced by a student so that students feel neglected and alienated, for that it takes some efforts to increase the sense of empathy of educators towards their students so that students feel These students feel cared for and with that can increase the confidence of students to share what is in the heart of an educator, for that we as high quality educators and professional educators must have a high empathy attitude, so what do you want to do ? by educators will be exemplified for their students and also students will be reluctant or polite to their educators if an educator has a high attitude of empathy not only among students, students will be known but also among the community for that empathy is very good, good in the lives of students or educators.